The Urgency of Strengthening Consumer Legal Protection in E-Commerce Transactions in Indonesia - Anggawira Anggawira; Sudaryat Sudaryat; Ina Heliany (JURNAL AKTA, 2026)
The rapid expansion of the digital economy has transformed commercial transactions by increasing the use of e-commerce platforms, creating both greater convenience and new legal challenges for consumer protection. The development of e-commerce in Indonesia has facilitated transaction activities, but also poses various risks for consumers, such as fraud, personal data breaches, and product non-conformity. This study aims to analyze the legal framework for consumer protection, evaluate the effectiveness of regulations in guaranteeing digital consumer rights, and examine the implementation and challenges faced in e-commerce practices in Indonesia. The research method used is a normative juridical approach with a descriptive-analytical type of research, using primary and secondary legal materials. The results show that although regulations such as Law Number 8 of 1999 and Law Number 1 of 2024 have provided a strong legal basis, the effectiveness of consumer protection is still not optimal. This is due to weak supervision, low consumer literacy, and a gap between regulations and practice in the field. Therefore, regulatory harmonization, strengthened law enforcement, and increased digital literacy are needed to realize effective consumer protection in the digital era.